2020
DOI: 10.1186/s12915-020-00808-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome assembly of the basket willow, Salix viminalis, reveals earliest stages of sex chromosome expansion

Abstract: Background: Sex chromosomes have evolved independently multiple times in eukaryotes and are therefore considered a prime example of convergent genome evolution. Sex chromosomes are known to emerge after recombination is halted between a homologous pair of chromosomes, and this leads to a range of non-adaptive modifications causing gradual degeneration and gene loss on the sex-limited chromosome. However, the proximal causes of recombination suppression and the pace at which degeneration subsequently occurs rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 136 publications
(198 reference statements)
4
67
2
Order By: Relevance
“…purpurea (Almeida et al 2020;Zhou et al 2020). No such gene is present in the Z-linked region of S. viminalis, consistent with the finding in the Populus species that the duplication is carried only in the Y-and not the X-linked region.…”
Section: Gene Content Evolution In the S Dunnii X-linked Regionsupporting
confidence: 88%
See 2 more Smart Citations
“…purpurea (Almeida et al 2020;Zhou et al 2020). No such gene is present in the Z-linked region of S. viminalis, consistent with the finding in the Populus species that the duplication is carried only in the Y-and not the X-linked region.…”
Section: Gene Content Evolution In the S Dunnii X-linked Regionsupporting
confidence: 88%
“…tremula (Müller et al 2020;Xue et al 2020). In two species of the Salix Chamaetia-Vetrix clade (S. purpurea and S. viminalis), a similar gene has been detected in the W-linked region of chromosome 15, and a partial and non-functional copy was found in the Z-linked region of the S. purpurea chromosome 15 (Almeida et al 2020;Yang et al 2020;Zhou et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromosome number of willows and poplars is the same, and they do not exhibit a morphologically differentiated sex chromosome 9,10 . The Salicaceae family, whose young sex chromosomes have evolved from different autosomes, provides a valuable comparative system for studying sex differentiation in plants 11 . Multiple studies have reported that chromosome XIX is the incipient sex chromosome in poplars 12 , and both XX/ XY 13,14 and ZW/ZZ 12,15 sex determination systems have been observed in different poplar species.…”
Section: Introductionmentioning
confidence: 99%
“…Further study showed that the SDR in S. viminalis is of limited size (~804 kb) and exhibits a higher SNP density in females 25 . Pseudogenization and the accumulation of repetitive elements in the SDR suggest that the fundamental process of sex chromosome formation occurred very swiftly after recombination ceased 11 . In a recent study, the SDR of S. purpurea was found to contain large palindromic repeats, and the SpRR9 gene was considered a putative candidate for controlling sex determination through the modulation of the cytokinin signaling pathway 26 .…”
Section: Introductionmentioning
confidence: 99%